An Analysis of Students’ Obstacles in Learning English for Grade VIII Students at SMP Negeri 1 Selesai - Anindya Nabila; Desi Triana Ayunsari; Resa Kristianda; Edi Suprayetno (English Lecturers and Teachers Association (ELTA), 2024)
This research explores the obstacles faced by students at SMP Negeri 1 SELESAI in learning English, particularly in reading. The study was conducted through preliminary analysis and a questionnaire, revealing a strong preference among students for topics related to the internet and entertainment, which might distract them from focusing on reading English materials. The research also revealed that students prefer to learn in groups rather than individually, suggesting a strong influence of peer interactions. Despite the high interest in English, students still face numerous obstacles in their learning process, including a lack of understanding about word distribution and pronoun usage in English, and difficulty in understanding and interpreting complex terms and phrases. The study suggests potential solutions to overcome these challenges, such as the use of more varied and interesting teaching methods, increasing students' understanding of English sentence structure, and enhancing students' interest and motivation in learning English, especially in reading. Keywords: Obstacle;, English learning; motivation